Reduced dream-recall frequency in left-handed adolescents: A replication - Mark Blagrove (Laterality: Asymmetries of Body, Brain and Cognition, 2014)
The ability to recall a dream upon waking up in the morning has been linked to a broad variety of factors such as personality, creativity, sleep behaviour and cognitive function. There have been conflicting findings as to whether dream recall is related more to the right or to the left hemisphere, and conflicting findings regarding the relationship of dream-recall frequency to handedness. We have found previously that right- and mixed-handers report having more dreams than left-handers, a finding more pronounced among adolescents than adults. In the present sample of 3535 participants aged from 6 to 18 years, right-handedness and mixed/inconsistent handedness were associated with higher dream-recall frequency compared to that of left-handed persons, again especially in adolescents compared with children. Further research is required to uncover the reason for the lower frequency of dream recall by left-handers.